84.9k views
2 votes
Complete the steps to solve the equation.

3x - 6(5x + 3) = 9x + 6


1. The distributive property:      3x - 30x - 18 = 9x + 6


2. Combine like terms:        -27x - 18 = 9x + 6


3. Addition property of equality:    -18 = 36x + 6


4. Subtraction property of equality:   -24 = 36x


5. Division property of equality: x = ?

User HankCa
by
5.2k points

2 Answers

5 votes

Answer:

-2/3

Explanation:

edge2020

User Wasyster
by
5.8k points
1 vote

Answer:

x=-2/3

Explanation:

3x-6(5x+3)=9x+6

3x-30x-18=9x+6

-27x-18=9x+6

-27x-9x-18=6

-36x-18=6

-36x=6+18

-36x=24

x=-24/36

simplify

x=-2/3

User Rubi
by
6.1k points